Fiscalism as Spending and Monetary Integration - Masudul Alam Choudhury; Noreha Halid; Mohammed Saleh Ahmed; Mohammad Shahadat Hossain (International Journal of Management Studies, 2013)
Macroeconomic policy coordination and the fi eld of micro-foundation of the macroeconomic theory have been riddled with the contest of claimed effi cacy between the Keynesian school and the monetarist school. Keynesianism upheld the predominance of fi scalism (spending) in economic stabilization on the one side. Friedman’s monetarist theory vouched for the same on the other side. As a result of the monetary and fi scal contest between the two schools a convergence between them could not be att ained. Such a divide is similar in economic science as it has been a fi asco thus far in the physical sciences between Quantum Mechanics explaining the small world phenomenon, and Relativity Physics explaining the large world phenomenon. The nonhomogenous views of a unique reality in economics, as in science, have defied the unifi cation of theories and application for the greater objective of wellbeing in an embedded social economy, beyond sheer address of the stabilization question. Our paper strides out in the new direction of a socioscientific epistemological worldview of the unifi cation of monetary and fi scal (spending) regimes in a consolidated theory of complementarities between them. The paper does this by breaking new grounds that are based on the model of organic unity of knowledge, which acts upon the simulation of well being with the method of circular causation. A review of the literature and introduction of formalism are undertaken to expound the theme of economic stabilization by means of complementing monetary and fi scal (spending) regimes in a unifi ed theory, while addressing the simulation of well-being in a learning model of unity of knowledge. The emergent methodology presents the description of a system of inter-variables circular causation relations. An extensive review of the literature is undertaken. An empirical presentation and a case study establish the validity of the well-being model with circular causation.